2010
DOI: 10.1002/app.33466
|View full text |Cite
|
Sign up to set email alerts
|

Novel dynamic vulcanization of polyethylene and ozonolysed natural rubber blends: Effect of curing system and blending ratio

Abstract: Dynamic vulcanization was studied in terms of the change in a-relaxation temperatures of the LDPE matrix, morphology, and mechanical properties of LDPE/ozonolysed NR blends which were vulcanized at various blend ratios and with different curing systems, i.e., peroxide and sulfur systems. The ozonolysed NR with M w ¼ 8.30 Â 10 5 g mol À1 and M n ¼ 2.62 Â 10 5 g mol À1 , prepared by the in situ ozonolysis reaction of natural rubber latex, was used in this study. The significant change in the a-relaxation tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The important peaks corresponding to the chloroacetate group showed at δ 1.31 ppm for CH 3 C, at δ 3.64 ppm for COH, and at δ 4.09 ppm for CH 2 Cl as analyzed by 1 H‐NMR [Figure (a)] and at δ 40.30 ppm (q) for CH 2 Cl and at δ 70.46 ppm (r) for COH as analyzed by 13 C‐NMR [Figure (b)]. The interpretation of the chloroacetate peaks was in agreement with previous reports,_ENREF_19 , though the CO peak was not observed because of the drastically high number‐average molecular weight of the CNR molecule, which is about 8.3 × 10 5 g/mol …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The important peaks corresponding to the chloroacetate group showed at δ 1.31 ppm for CH 3 C, at δ 3.64 ppm for COH, and at δ 4.09 ppm for CH 2 Cl as analyzed by 1 H‐NMR [Figure (a)] and at δ 40.30 ppm (q) for CH 2 Cl and at δ 70.46 ppm (r) for COH as analyzed by 13 C‐NMR [Figure (b)]. The interpretation of the chloroacetate peaks was in agreement with previous reports,_ENREF_19 , though the CO peak was not observed because of the drastically high number‐average molecular weight of the CNR molecule, which is about 8.3 × 10 5 g/mol …”
Section: Resultssupporting
confidence: 90%
“…The interpretation of the chloroacetate peaks was in agreement with previous reports, 19,20 _ENREF_19 ,21 though the C@O peak was not observed because of the drastically high number-average molecular weight of the CNR molecule, which is about 8.3 3 10 5 g/mol. 22 From the molecular structure characterized by the FTIR and NMR techniques, the molecular structure of the CNR chemically modified from the NRL was clarified to be composed of multifunctional groups including epoxy and hydroxyl present on the main chain and the chloroacetate present as pendant groups of a rubber molecule. The proposed mechanism of the chemical modification of NR producing the CNR is as shown in Figure 3.…”
Section: Characterization Of Chloroacetated Natural Rubbermentioning
confidence: 99%
“…As PHBV and NR are inherently immiscible due to entropy constraints (strong polarity differences), the interfacial adhesion existing between the two phases is probably caused by polymer crosslinking, at low loadings including PHBV grafts onto NR, while at high loadings these are probably mostly NR‐NR crosslinks. PHBV molecules may entangle across PHBV and NR interfaces and lock in loops inside the NR network . The restricted crystallization behavior of the PHBV in the blends observed in DSC was partially caused by restricted movement of the PHBV molecular chains locked within localized NR networks.…”
Section: Resultsmentioning
confidence: 97%
“…12 Sulphur and peroxide vulcanising systems employed in ozonolysed NR/LDPE (40/60) blends revealed that the sulphur vulcanising system provides a higher degree of crosslink density than the peroxide vulcanising system, and attributed to improved damping and homogeneous phase morphology. 13 However, the blends with the peroxide vulcanising system showed relatively enhanced tensile strength and elongation at break. Furthermore, tensile strength, elongation at break and damping properties of the blends vulcanised with both systems improved with the increasing ozonolysed NR content.…”
Section: Introductionmentioning
confidence: 96%